Literature Review: The Effectiveness of The Realistic Mathematics Education Approach to Improve Students Mathematical Communication Skills - Annisa, Delsyifa Putri; Kadarisma, Gida; Afrilianto, M. ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Communication is one of the important skills that students must have in mathematics. Engaging in communication activities helps provide an understanding of mathematical communication skills to students. However, in reality, students' mathematical communication skills are still in the low category. Therefore, a more interactive learning method is needed. This study was conducted to analyze the effectiveness of the Realistic Mathematics Education (RME) approach in improving mathematical communication skills.The method used in this research is a literature review with inclusion and exclusion criteria focusing on studies containing quantitative or qualitative data. The data collection technique involved gathering relevant National and International Journal articles published between 2019 and 2023. From the numerous articles found, researchers selected 21 articles related to this study. The data processing technique applied in this study examined the effectiveness of using Realistic Mathematics Education (RME)  to improve communication skills in the collected articles. The results showed that RME is an effective learning approach for improving students' mathematical communication skills. In addition to Realistic Mathematics Education (RME), classroom learning can be enhanced with various media, such as Audio Visual Media or Learner Worksheets (LKPD). This approach makes classroom learning more interactive and receives positive responses from students, helping them understand the material better by expressing mathematical ideas through oral and written language and making arguments with confidence.